Key And Derivative Indicators for Assessing the Quality of Lesson in Physics - Imanov Bakhtiyor Berdievich (Zien Journals, 2022)
The article discusses the indicators that assess the quality of physics lessons.Also, the necessary rules, guidelines and recommendations for the presentation of the subject of physics have been developed.
Keywords: Lesson; purpose; competence; scientific